Adsorption Analysis of Activated Carbon from Rice Husk and Kepok Banana (Saba Banana) Peel for Treating Ogan River Water - Kiagus Ahmad Roni; Erna Yuliwati (CHEMICA: Jurnal Teknik Kimia, 2020)
Ogan river has been utilized as source of raw water for various purposes. The quality of water needs to be monitored continuously. Nowadays, the Ogan River was polluted by household waste and industrial wastewater. This study aims to obtain a better adsorber of rice husks or kepok banana peels activated carbon for treating the Ogan river. Activated carbon is used in different states of applications after its discovery as a robust and reliable is adsorbent. The used method to produces activated carbon is pyrolysis, physical-chemical activation, and steam pyrolysis from agricultural waste materials, e.g., rice husk, palm oil shell, and banana peels. Activated carbon is applied in water treatment, significantly to reduce total suspended solids, pH, and heavy metal (iron) of the Ogan river. In this study, rice husk and kepok banana peels activated carbon were produced using chemical activation with H3PO4 0.1 N 20% at a temperature of 450 oC. The morphological and performance test was conducted on prepared activated carbon. The top surface area of both activated carbon was observed using a scanning electron microscope (SEM) and Fourier-transform infrared spectroscopy (FTIR) analysis. The mean pore size was calculated to describe the adsorption process of the ogan river, which indicated total suspended solids (TSS) and iron (Fe) concentration, then pH value. The results showed that kepok banana peels activated carbon reduced TSS levels of 79.3 to 48.2 mg/L, decreased Fe concentration of 0.63 to 0.07 mg/L, and increased pH value of 5.94 to 7.89. Meanwhile, the adsorption using activated carbon of rice husk could reduce TSS concentration of 79.3 to 36.1 mg/L, decrease Fe concentration of 0.63 to 0.01 mg/L and increase the pH value increased from 5.94 to 7.16. It was concluded that the activated carbon of rice husks has better performance than kepok banana peels.